Using R in Research Classes: - Hanni Flaherty; Christine Vyshedsky; Charles Auerbach (Journal of the Scholarship of Teaching and Learning)
Engaging in anti-oppressive, evidence-based practice in the social work field demands preparation for research methods during social work education. However, while faculty members at institutions of higher education have access to more technology than ever before and teach graduate students who use technology constantly in their personal lives, barriers still exist that limit the implementation of these new technologies, despite benefits in accessibility and equity in doing so. This study examined faculty members' perspectives related to their use of R as a free statistical analysis tool in their teaching of research classes. Findings indicated that the primary barriers included faculty perceptions of the technology.